Świadomość czy samoświadomość ubezpieczonych - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2010)
There is a term ‘self-avareness’ in the literature of insurance and opinion on the insurance market. On the base of the insurance data it is concluded that Poles hale a low level of awareness. The level increases when random event occurs. The aim of his article is an attempt to define a term ‘self-awareness’ and point its connection with life and property insurances.